Marijuana use and its correlates among school-going Jamaican adolescents: a finding from a national survey - Dadras, Omid (Frontiers in Psychiatry, 2024)
Introduction The recent data indicate almost a fifth of Jamaican adolescents used marijuana in the past 30 days. To ensure the optimal allocation of resources, a country-specific understanding of factors associated with marijuana use among adolescents is essential. Therefore, this study aimed to address this gap among adolescents aged 13–17 years in Jamaica. Methods We analyzed data from the recent Jamaica Global School-Based Student Health Survey conducted in 2017. The sample consists of school-going Jamaican adolescents of 7th−12th grades. The prevalence of recent marijuana use was assessed and compared across different demographics, substance use, and risk behaviors using bivariate and multivariable logistic regression analyses. Results Older adolescents and men had a higher likelihood of recent marijuana use. Psychosocial risks, such as loneliness, frequent worry, suicidal ideation, physical attacks, and school absenteeism, were associated with higher marijuana usage. Parental smoking increased the odds, whereas strong parental support and awareness decreased it. Other substance uses, especially amphetamine and tobacco products, had strong associations with marijuana use. Early initiation of substances was associated with a higher risk of marijuana use. Sexually active adolescents, especially those initiated before the age of 14 years, had higher rates of marijuana use. Conclusion The intricate link between harmful and supportive psychosomatic and risk behaviors with recent marijuana use highlights the importance of holistic interventions and policies focusing on emotional health, parental guidance, substance education, and sexual activity implications.